STRICT LIABILITY KORPORASI TERHADAP KEJAHATAN BISNIS - Setiady, Tri; Hidayat, Taufik (Yustitia, 2024)
The potential for crime in the economic sector in the era of globalization can occur carried out by business actors in the form of corporations that can cause losses and victims, supported by the emergence and development of science and information technology. The development of technology along with freedom of information / press, makes the public so enthusiastic with all forms of business development that are instant and practical without requiring a long time or process that can be done at home using gadgets. According to the identification theory of the actions of the management or employees as personnel of a corporation identified as corporate actions, the actions of the management which are the directing mind of a corporation are identified as corporate actions so that criminal acts committed by the management are responsible, the crime can be charged to the corporation.